Use of bacteriophage P1 as a vector for Tn5 insertion mutagenesis. - Quinto, M (1984)
Infection of a strain lysogenic for bacteriophage P1 CM with P1::Tn5 followed by simultaneous selection for the chloroamphenicol resistance associated with the resident prophage and the kanamycin resistance associated with Tn5 results in a large number of independent Tn5 insertion mutations. This superinfection-selection protocol is a fast, easy, and safe way to isolate null mutations in enteric bacteria without generating unwanted cryptic mutations elsewhere in the genome.